RNAi‐mediated reduction of hepatic Tmprss6 diminishes anemia and secondary iron overload in a splenectomized mouse model of β‐thalassemia intermedia. Issue 6 (23rd March 2018) - Schmidt, Paul J.; Liu, Kaifeng; Visner, Gary; Fitzgerald, Kevin; Fishman, Shannon; Racie, Tim; Hettinger, Julia L.; Butler, James S.; Fleming, Mark D.
Abstract: Diminished β‐globin synthesis in β‐thalassemia is associated with ineffective erythropoiesis, leading to secondary iron overload caused by inappropriately low levels of hepcidin and to splenomegaly in the symptomatic thalassemias. Splenectomy is often employed in patients with β‐thalassemia to reduce hemolysis. Expression of the iron regulatory peptide hormone hepcidin is repressed by the serine protease TMPRSS6 . Hepcidin induction by RNAi‐mediated inhibition of TMPRSS6 expression reduces iron overload and mitigates anemia in murine models of β‐thalassemia intermedia. To interrogate the efficacy of RNAi‐mediated reduction of Tmprss6 in splenectomized β‐thalassemia, splenectomized β‐thalassemic Hbb th3/+ animals were treated with a GalNAc‐conjugated siRNA targeting Tmprss6 (GalNAc‐Tmprss6) and their hematological and iron parameters monitored. We demonstrate that treatment with GalNAc‐Tmprss6 significantly diminishes Tmprss6 expression and appropriately elevates hepcidin expression in splenectomized Hbb th3/+ animals. Similar to unsplenectomized animals, treated animals have markedly improved anemia due to diminished ineffective erythropoiesis and reduced iron loading in both serum and tissue. These results suggest that RNAi‐mediated reduction of Tmprss6 may have positive outcomes even in splenectomized β‐thalassemia patients.